2016
DOI: 10.1371/journal.pone.0156479
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Regularized Logistic Regression Privately and Efficiently

Abstract: As one of the most popular statistical and machine learning models, logistic regression with regularization has found wide adoption in biomedicine, social sciences, information technology, and so on. These domains often involve data of human subjects that are contingent upon strict privacy regulations. Concerns over data privacy make it increasingly difficult to coordinate and conduct large-scale collaborative studies, which typically rely on cross-institution data sharing and joint analysis. Our work here foc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 45 publications
(129 reference statements)
1
24
0
Order By: Relevance
“…This demonstrated that the performance of machine learning methods largely depended on the application scenario [26]. RLR, as a classical machine learning method with its flexibility and simplicity [27], showed quite a good performance in our study. SVM is also a powerful machine learning method [13], and it also showed excellent performance in the ROS-balanced data set in our study.…”
Section: Discussionsupporting
confidence: 51%
“…This demonstrated that the performance of machine learning methods largely depended on the application scenario [26]. RLR, as a classical machine learning method with its flexibility and simplicity [27], showed quite a good performance in our study. SVM is also a powerful machine learning method [13], and it also showed excellent performance in the ROS-balanced data set in our study.…”
Section: Discussionsupporting
confidence: 51%
“…All these measurement issues are common to studies of this type, and should not substantially affect the overall research findings. Besides, more advanced model such as regularized logistic regression [ 43 ] may be more effective when too many factors in model, which should be tried to be used in the future research. Last but not the least, the results of the present study were limited because of the relatively young age of the subjects, and should therefore be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%
“…These classification models are frequently utilized in a wide range of fields, and are recognized as popular choices for classification tasks [20,21,37]. …”
Section: Methodsmentioning
confidence: 99%